Development of tamarind (Tamarindus indica linn) leaf jelly - Dulaugon, Katherine Romero (2006.)
The utilization of juice extract from tamarind leaf for jelly making was investigated.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Tamarind; Leaf jelly